Macrostructure Analysis of Indonesia's National Songs: Searching for their Ideologies - Aylanda Hidayati Dwi-Nugroho (Master Program in Linguistics, Diponegoro University, 2025)
This study investigates the underlying ideologies in twelve Indonesian compulsory national songs through the lens of Critical Discourse Analysis (CDA). By analysing the microstructure (the linguistic features), the macrostructure (the themes and messages), and the resulting mental representations, this research reveals how the national songs serve as powerful tools for constructing and reinforcing a number of ideologies. These patriotic songs, which were composed around 1927-1961, are not merely cultural artefacts, but ideological instruments that confirm Indonesia’s national identity and culture, build national pride and patriotism, strengthen national sovereignty and independence, and foster a sense of national duty and responsibility. These ideologies have made these songs so iconic that they are still sung in public when Indonesia celebrates its independence to this day. This paper suggests that future studies need to investigate why new Indonesian national songs which are more relevant and connected to the current generations are very few.